Satisfaction towards the administration of Ban Burnapiya School under the Primary Educational Service Area Office 1 - Yaka, Halim (Al-HIKMAH Journal, 2021)
The purpose of this research were to: 1) Study parents satisfaction towards the administration of Ban Burnapiya School under the Primary Educational Service Area Office 1, 2) Study the administration of Ban Burnapiya School, The samples used in this research were Parents of Ban Burnapiya School by 78 people. The statistics used for data analysis were frequency value, percentage, mean and standard deviation. The research found that: 1) Parents are satisfied with the administration of the Ban Burnapiya School at the middle level. 2) The parents showed the satisfaction of the administration of Ban Burnapiya School in all aspects difference and statistically significant at the .05 level. The comparison of satisfaction of different level of education showed different and comparison of satisfaction of different occupation showed no different.